Supply chain outsourcing in response to manmade and natural disasters in Colombia, a humanitarian logistics perspective (2015)
ABSTRACT: This paper analyses the level of outsourcing among the actors of the humanitarian response system to aid those impacted by natural disasters as well as the system to aid those impacted by the armed conflict in Colombia. Based on reports produced by the actors involved, in addition to several interviews conducted with individuals directly involved in the relief operations, this paper characterizes the supply chain food aid distribution and analyses the implications drawn from the differences between the levels of outsourcing identified. Supply chains are codified in four segments for analysis purposes: logistics operations supporting the disaster area (upstream), in the disaster area (midstream), and to beneficiaries directly (downstream and last mile distribution as two individual segments). The number of third parties, whether humanitarian aid organizations or private contractors, participating in the supply chains as actors orchestrating food aid distribution to beneficiaries, drives the levels of outsourcing. Groups of supply chains from representative established organizations deploying a vast portion of food aid distribution are studied. These groups are analysed to illustrate differences and commonalties, and reach conclusions of general applicability. Based on the findings, the paper makes policy implications to increase performance of future food aid distribution operations in response to larger scale disasters as well as opportunities for future research.